Zoning Analysis of Settlement and Tourism in Kampung Melayu Terengganu - Vicky Lim; Nurhalisa Nurhalisa; Khayril Husnul; Steven Eli Marsela; Gladies Imanda Utami Rangkuty (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2023)
A city or region absolutely needs zoning or regional organization. One of them is Terengganu Malay Village Settlement Zone. Development without a clear regional organization and non-compliance with the rules for structuring coastal areas has caused Vanaküla's condition to worsen. The concept of good settlement management can support the ability of an area to maintain activity stability between visitors and the people who live in the area. The purpose of this research is to determine the zoning between the tourism area and Kampung Melayu, Terengganu, and to provide clear guidelines for more appropriate zoning. The method used in this study is a qualitative descriptive analysis method, where data collection techniques are used to carry out zone analysis at the location of the research object. The results of the study show that the Terengganu old village area can support the achievement of a sustainable zone in terms of construction and quality of the area that is laid out. Based on findings in old village settlements in Terengganu, it is classified as flexible zoning, so it has the potential to become a non-permanent zoning area, impacting residential areas which can change their use at any time.